Tourism destination marketing and information technology in Ghana - Kotoua, Selira; Ilkan, Mustafa (Elsevier, 2017)
A research model was developed to investigate the relationships between intention to visit and tourists' satisfaction as a source of mediation for travelers through information search and e-word of mouth. A judgmental sampling technique and a sample questionnaire survey of 350 respondents were involved in the research measurement. The finding of the analytical results indicates that the dimensions of tourists' satisfaction as a mediator affect the overall tourists' intention to visit. Simple websites no longer have an impact on destination marketing because of the advance in technology. Websites should provide different tools and marketing channels to facilitate the surfing and information needs of tourists. The research used the instruments of online word of mouth and information search by modifying the theory of planned behavior to consider the context of intention to visit. Valuable information for managers and researchers interested in the internet and online destination marketing is essential.
Keywords: eWOM; Ghana; Information search; Satisfactions; Visitation intentions